Daily Functional Characteristics and Health Among Older Adults During COVID-19: A Structural Equation Modeling Approach - Sara Rosenblum PhD; Ortal Cohen Elimelech MSc (SAGE Publishing, 2024)
Within a few years, 1 in 6 people will be aged 60 years or older. Extreme situations, such as the COVID-19 crisis, constitute a challenge to older adults. However, the literature on the daily functional characteristics of older adults in the past and during the COVID-19 crisis and their relationships to their physical and mental health is scarce. This study aimed to examine the past and present daily functional factors associated with physical and mental health in older adults. Using an online platform, 204 Israelis aged 60 years and older reported their physical health symptoms and anxiety levels. They completed questionnaires about past (negative life events and childhood daily functional self-actualization) and present (adulthood daily functional self-actualization, functional cognition and sleep quality) factors. Structural equation modeling revealed correlations between functional cognition and childhood daily functional self-actualization (β = −.18) and anxiety (β = .15); adulthood daily functional self-actualization and past negative life events (β = −.18), anxiety (β = −.50), and physical symptoms (β = −16); and sleep quality and past childhood daily functional self-actualization (β = −.19), negative life events (β = .22), anxiety (β = .18), and physical symptoms (β = .40). These findings shed light on potential functional factors for older adults' health, indicating that these functional factors play a vital role in reducing health problems in later life.